2012
DOI: 10.1155/2012/617918
|View full text |Cite
|
Sign up to set email alerts
|

Use of Chinese Medicine and Subsequent Surgery in Women with Uterine Fibroid: A Retrospective Cohort Study

Abstract: Background. Chinese medicine (CM) has been used to relieve symptoms relevant to uterine fibroids. Objective. This study investigated the association between the use of CM and the incidence of uterine surgery in women with uterine fibroids. Subjects and Methods. This retrospective cohort study extracted records for 16,690 subjects diagnosed with a uterine fibroid between 2000 and 2003 from the National Health Insurance reimbursement database. The risk factors for surgery were examined via Cox proportional hazar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 30 publications
2
12
0
Order By: Relevance
“…A comparison of socio-demographic factors between CM users and nonusers in the present study shows that CM users had higher income levels than CM nonusers among endometriosis patients. This coincides with another study that extracted subjects of the same disease from 1998 to 2008, 2 and of two other female-specific diseases: uterine fibroid and breast cancer 17,18 ; this phenomenon, however, does not exist among males. 13,19 This study also observed that subjects without childbirth experience were likely to use CM, in agreement with a previous report that found infertility to be a factor that drives patients to use CM.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…A comparison of socio-demographic factors between CM users and nonusers in the present study shows that CM users had higher income levels than CM nonusers among endometriosis patients. This coincides with another study that extracted subjects of the same disease from 1998 to 2008, 2 and of two other female-specific diseases: uterine fibroid and breast cancer 17,18 ; this phenomenon, however, does not exist among males. 13,19 This study also observed that subjects without childbirth experience were likely to use CM, in agreement with a previous report that found infertility to be a factor that drives patients to use CM.…”
Section: Discussionsupporting
confidence: 89%
“…13,19 This study also observed that subjects without childbirth experience were likely to use CM, in agreement with a previous report that found infertility to be a factor that drives patients to use CM. 17 As for co-morbidities, endometriosis patients who were co-morbid with dysmenorrhea tended to use CM more often than patients co-morbid with hypermenorrhea or iron-deficient anemia. This implies that CM might have uneven effectiveness of CM on these three co-morbidities in endometriosis.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Shih C-C et al 23) 2012 33) In 1997∼2010, 9.25% patients with newly diagnosed acute myeloid leukemia and received radiotherapy and chemotherapy used TEAM 34) Colon cancer In 2004∼2008, 19.81% of newly diagnosed colon cancer patients used TEAM 35) In 2007, 26.9% of newly diagnosed colorectal cancer patients used TEAM 36) Head and neck cancer In 2000∼2011, 37.51% of newly diagnosed head and neck cancer patients used TEAM 37) Pediatric cancer In 2001∼2011, 62.37% of newly diagnosed pediatric cancer patients used TEAM 38) Breast cancer In 1999∼2008, 81.55% of newly diagnosed breast cancer patients used TEAM 39) In 2007, 35.6% of breast cancer patients used TEAM 40) In 2009, 37.33% of breast cancer patients used TEAM 41) Uterine fibroid In 2000∼2003, 73.33% of newly diagnosed uterine fibroid patients used TEAM 42) In 1996∼2010, 25.84% of uterine fibroid patients used TEAM 43) In 2002∼2010, 87.08% of newly diagnosed uterine fibroid patients used TEAM 44) Prostate cancer In 1996∼2008, 38.8% of prostate cancer patients used TEAM 45) In 1998∼2003, 64.5% of newly diagnosed prostate cancer patients used TEAM 46) In 2003∼2008, 52.6% of prostate cancer patients used TEAM 47) In 2007, 22.4% of outpatients with prostate cancer received prescription of herbal medicine 48) Lung cancer In 1996∼2010, Of the lung cancer patients, 31.17% of the operation patients and 26.32% of the non-operation patients used TEAM 49) Endocrine, nutritional and metabolic diseases, and immunity disorders (3.59%) Hyperlipidemia In 2003∼2009, 82.95% of hyperlipidemia patients used TEAM 50) Diabetes mellitus In 2000∼2011, 20.55% of type I diabetes mellitus patients used TEAM 51) In 1998∼2008, 77.91% of newly diagnosed type II diabetes mellitus adult patients used TEAM 52) Mental disorders (3.10%)…”
Section: 대만의 보편적 Team 이용 관련 연구mentioning
confidence: 99%
“…Chinese medicine (CM) is an alternative and complementary medicine to treat gynecological diseases in Asian countries [ 8 - 10 ]. Among fibroid patients, three fourth of them have the experience of utilizing CM, which are considered to be with fewer side effects, less expensive [ 11 , 12 ], less subsequent surgery rate [ 13 ], and higher life quality than conventional western medicine [ 14 ]. Because of the high usage rate, the expense of CM in Taiwan has been covered by the government-run National Health Insurance (NHI) system since 1995 [ 15 ].…”
Section: Introductionmentioning
confidence: 99%